The Role of Polymerase Chain Reaction (PCR) in Diagnosis of Spine Tuberculosis after Pre-operative Anti-tuberculosis Treatment - Ahmad Hata, Rasit; SF, Ibrahim; CC, Wong (Malaysian Orthopaedic Association, 2011)
Objective: